Analysis of the relationship of water quality to total hemocytes in intensive ponds for vannamei shrimp (Litopenaeus vannamei) cultivation CV TTB, Pasuruan City, East Java - Rahmahnia Febriyani; Muhammad Musa; Mohammad Mahmudi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
One type of shrimp that is quite potential to be developed is the vannamei shrimp (Litopenaeus vannamei). This cultivation is developing with intensive technology. This study aims to analyze the relationship between water quality and total hemocyte shrimp in vannamei shrimp aquaculture ponds. Parameters measured include physical and chemical parameters, namely temperature, brightness, pH, dissolved oxygen, TSS, BOD, ammonia. while to see the health of shrimp seen by calculating the total hemocytes (THC) of shrimp. The results showed that the overall range of water quality obtained was still in a suitable condition for cultivation activities, while the highest hemocyte value was obtained from the sample in the 3rd sampling which reached a value of 3.74 x 106 mg/l. Based on the results of the linear regression test, it was found that the TSS and BOD parameters were significantly correlated with total hemocytes in vannamei shrimp (Sig. 0.05), it can be concluded that the relationship between water quality parameters that affect total hemocyte is BOD and TSS